Plasmapheresis and Steroid Treatment of Levamisole-Induced Vasculopathy and Associated Skin Necrosis in Crack/Cocaine Users. Issue 2 (March 2013) - Pavenski, Katerina; Vandenberghe, Hilde; Jakubovic, Henry; Adam, David N.; Garvey, Bernadette; Streutker, Catherine J.
Background: Levamisole was removed from the market due to complications of agranulocytosis and skin necrosis. Levamisole has been reported in a high proportion of seized cocaine in North America and has been associated with multiple cases of skin necrosis. Objective: We report three cases of levamisole/cocaine-induced skin necrosis who responded to treatment with plasmapheresis and immunosuppression. Results: Three patients presented with painful necrotic skin lesions on the ears, cheeks, breasts, and buttocks. The extremities were involved in two patients and the upper respiratory tract mucosa in one patient. All had markers of immune activation, with elevated C-reactive protein, antinuclear antibody, and perinuclear antineutrophil cytoplasmic antibody. Skin biopsy in all cases revealed a mixed pattern of thrombosis and vasculitis within dermal vessels, with overlying ischemic ulceration of skin and soft tissues. One patient required extensive debridement of the skin and soft tissue of the calves and also had respiratory involvement. All patients were treated with plasmapheresis and immunosuppression with rapid stabilization and/or improvement of the lesions. Conclusion: Levamisole is frequently added to crack/cocaine; we report three patients who developed vascular lesions and skin necrosis after using cocaine/levamisole. These improved with plasmapheresis and immunosuppression as well as abstention from the drugs; one patient with severe disease required debridement and skin grafting.